Dominant lethal test in rats treated with some plant extracts - Aritajat S. (2014)
The present study was undertaken to investigate the toxic effect of aqueous extracts of Aegle marmelos (AM), Stevia rebaudiana (SR), Pouteria cambodiana (PC) and Clausena excavata (CE) on rats by dominant lethal test. The data of 8-week treatment suggested that none of the extracts adversely affected male body and testicular weights as well as cauda epididymal sperm counts. No notable changes in sperm morphology and motility were observed. On the other hand, sperm count in the CE group was significantly higher as compared to both control and other treatment groups. There were no abnormal changes in the number of implantation sites, number of viable fetuses and number of dead fetuses in females mated with plant extract-treated males relative to controls. Based on these results, it could be concluded that all the investigated plant extracts have no toxic effect on male rat reproduction and progeny outcome.